Ecological aspects of Sphaeroceridae (Diptera: Acalyptratae) in dry tropical forest of the Colombian Caribbean. (2017)
Sphaeroceridae is associated with a wide variety of anthropogenic and natural habitats. In Colombia this group has not been studied extensively, therefore the purpose of this investigation was to determine the genera present in the tropical dry forest ecosystem in the Colombian Caribbean coast and some ecological aspects in relation to nycthemeral activity, habitat and bait preference. Three environments (urban, rural and forest), from the departments of Cesar, Cordoba and Magdalena were sampled using van Someren Rydon traps baited with human feces, decomposing fish and decomposing fruit. Nine traps were placed in each department, with one per bait and ecosystem, over a period of 72 hours,with collection taking place every 12 hours. In total 147 individuals belonging to six genera were obtained of which Archiceroptera and Bromeloecia are new records for Colombia.